2015
DOI: 10.11646/zootaxa.3985.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics, diversification, and systematics of Tibicen Latreille 1825 and allied cicadas of the tribe Cryptotympanini, with three new genera and emphasis on species from the USA and Canada<br />(Hemiptera: Auchenorrhyncha: Cicadidae)

Abstract: North America has a diverse cicada fauna with multiple genera from all three Cicadidae subfamilies, yet molecular phylogenetic analyses have been completed only for the well-studied periodical cicadas (Magicicada Davis). The genus Tibicen Latreille, a large group of charismatic species, is in need of such work because morphological patterns suggest multiple groups with complicated relationships to other genera in the tribe Cryptotympanini. In this paper we present a molecular phylogenetic analysis, based on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…1 and Results). Although the "narrowly V-shaped" eighth sternite described by Lee is more acutely angled than in other Neotibicen, it is close to that found in N. davisi harnedi (Davis) and N. davisi davisi (Smith and Grossbeck) (see also Hill et al 2015). Sanborn and Heath (2017) have noted as well that intraspecific variation in the shape of the eighth sternite causes problems for generic definitions based on single specimens.…”
Section: Synonymy Of Paratibicensupporting
confidence: 67%
See 3 more Smart Citations
“…1 and Results). Although the "narrowly V-shaped" eighth sternite described by Lee is more acutely angled than in other Neotibicen, it is close to that found in N. davisi harnedi (Davis) and N. davisi davisi (Smith and Grossbeck) (see also Hill et al 2015). Sanborn and Heath (2017) have noted as well that intraspecific variation in the shape of the eighth sternite causes problems for generic definitions based on single specimens.…”
Section: Synonymy Of Paratibicensupporting
confidence: 67%
“…Other than the highly distinctive uncus, which was noted by earlier authors (Davis 1922;Hill et al 2015;Smith & Grossbeck 1907), the genitalic characters identified by Lee are subtle and unlikely to be applied consistently (see pygofer images in Supplementary Fig. 1).…”
Section: Synonymy Of Paratibicenmentioning
confidence: 83%
See 2 more Smart Citations
“…These data suggest that J. coenia bergi has a North American geographic origin and is a descendant of mainland populations of J. coenia coenia . In this regard, J. coenia bergi is similar to many other endemic species, such as the Bermuda skink ( Plestiodon longirostris ) (Brandley et al , ), Bermuda cicada ( Tibicen bermudiana ) (Hill et al , ), Bermuda cedar ( Juniperus bermudiana ) (Guo et al , ), and Bermuda palmetto ( Sabal bermudana ) (Heyduk et al , ), all of which appear to have colonized Bermuda from the North American mainland. That being said, at least one endemic species, the Bermuda petrel ( Pterodroma cahow ), appears to be more closely related to species from the Caribbean and the islands of the eastern Atlantic than to species from the North American mainland (Welch et al , ).…”
Section: Discussionmentioning
confidence: 89%